(untitled) (American Journal of Islam and Society, 1988)
I. Introductory Remarks One of the bounties bestowed on Muslims by Allah (SWT) is the Shari’ah: the Divine guidance and code of conduct, necessary to achieve success in this world and the world hereafter. For the colonists who subjugated Muslim lands it appeared necessary therefore to first deprive Muslims of their source of sustenance and symbol of identity. The first target of their attack was the Shari’ah; every aspect of which was ridiculed, belittled or truncated. It is difficult to improve upon Isma’il Raji al Faruqi‘s graphic description of this onslaught. He who wrote: By the colonialists directly, or by their native stooges, everything Islamic fell under attack. The integrity of the Qur’anic text, the genuineness of the Prophet (SAAS), the veracity of his Sunnah, the perfection of the Sharibh the glories of Muslim achievements in culture and civilization - none of them was spared. The purpose was to inject doubt in the Muslim’s confidence in himself . . . to subvert his Islamic personality . . . lacking the spiritual stamina necessary for resistance . . . the Muslim was turned into something neither Islamic nor Western, a cultural monstrosity of modem times ...